Advance Directives in the Nursing Home Setting: An Initiative to Increase Completion and Reduce Potentially Avoidable Hospitalizations. Issue 1 (2nd January 2021) - Galambos, Colleen; Rantz, Marilyn; Popejoy, Lori; Ge, Bin; Petroski, Greg
Abstract: Advance directive (AD) completion can improve transitions between hospitals and skilled nursing facilities (SNF's). One Centers for Medicare and Medicaid Services (CMS) Innovations Demonstration Project, The Missouri Quality Initiative (MOQI), focused on improving AD documentation and use in sixteen SNF's. The intervention included education, training, consultation and improvements to discussion process, policy development, increased AD enactment, and increased community education and awareness activities. An analysis was conducted of data collected from annual chart inventories occurring over four years. Using a logistic mixed model, results indicated statistical significance ( p  < .001) for increased AD documentation. Greatest gains occurred at project mid-point. The relationship between having an AD and occurrence of transfer to a hospital was tested on a sample of 1, 563 residents with length of stays more than 30 days. Residents who did not have an AD were 29% more likely to be transferred. A logistic regression was conducted, and the results were statistically significant ( p  < .02).